PENGGUNAAN MEDIA INTERAKTIF UNTUK MENINGKATKAN KONSENTRASI SISWA KELAS 2 PADA JAM TERAKHIR DI SD INPRES 3 BIROBULI - Yuana Stesya Palunsu; Sitti Rahmawati; Suhestin Mooduto (EDU RESEARCH, 2024)
The purpose of this study is to enhance the learning focus of second-grade students at SD Inpres 3 Birobuli during the final hour of the school day through the use of interactive, technology-based media. In the last learning sessions, students often experience a decline in concentration and active participation. To address this issue, various interactive media were utilized, such as educational games, interactive learning videos, and engaging digital applications. This study employs Classroom Action Research (CAR) with two cycles, including planning, action, observation, and reflection phases. Each cycle aimed to identify improvements in students' focus during the learning process. The results indicate a significant increase in student focus and active participation, particularly during the last hour of learning, following the implementation of interactive media. The application of interactive media has proven to be an effective way to maintain student engagement until the end of the learning day, ensuring better achievement of learning objectives.